Relationship between Wheat Yield and Yield Attributing Character at Late Sowing Condition - Jaisi, Sushil; Thapa, Asha; Poudel, Mukti Ram; Gairhe, Hari Prasad; Budathoki, Keshab Kumar; Karki, Binod (Indonesian Journal of Agricultural Research, 2021)
Correlation coefficient and path analysis were computed between yield and yield attributing trait among twenty genotypes of wheat. The research was conducted during winter season of 2020/2021 in the agronomic field of the Institute of Agriculture and Animal Science (IAAS), Bhairahawa, Nepal to identify the traits which influence the positive and negative relation to grain yield. Twenty genotypes of wheat were sown on 24th December 2020 on alpha lattice design with two replications. It has been found that under heat stress, DTB, DTH, DTM, CLC, PH, NGPS show a non-significant positive correlation with GY. Similarly ET shows a highly significant positive correlation to GY. However, SL, SW, TKW have a non-significant negative correlation with GY. In path analysis, DTM and ET have a positive direct effect on GY and DTH, SL, CLC and NGPS have an indirect effect on GY. Hence, the ET and DTM can be used to select wheat genotype for breeding purpose and studies to improve yield of genotypes under heat stress condition.